Passivity-Based Control Strategy for Single-Phase Three-Level T-Type PWM Rectifiers - Komurcugil, Hasan; Bayhan, Sertac (IEEE, 2020)
This paper presents a passivity-based control (PBC) strategy for single-phase three-level T-type rectifiers. The proposed PBC strategy is based on energy shaping and damping injection. First of all, in order to decide about the type of damping injection, the mathematical model of the rectifier is derived. Then, the control input, from which the pulse width modulation signals are produced, is obtained from this model. Based on the obtained mathematical model, the damping injection is applied accordingly. The amplitude of reference grid current is calculated from the power balance equation of the rectifier. In order to satisfy the unity power factor requirement, the calculated reference amplitude is multiplied by the sinusoidal waveform template generated from the grid supply. The performance of the proposed PBC strategy is investigated by simulations during steady-state and transient due to the load change. It is shown that the dc output voltage is regulated at desired level and grid current tracks its reference in both cases.
IEEE 29th International Symposium on Industrial Electronics (ISIE) -- JUN 17-19, 2020 -- ELECTR NETWORK
Keywords: Three-level T-type rectifier; passivity-based control; damping injection